Emergency Dakwah dalam Mebangun Mental Spiritual Masyarakat (Tinjauan Tafsiran Surat Al-Ikhlash) - Iman, Sunardi Bashri (AT-TAWASUL, 2025)
Da'wah on social media that aims only to seek popularity, viral obsession, and earn lots of money is a bad act, contrary to the principle of monotheism. The above behavior encourages ignoring the validity of information that is contrary to the spiritual mental development of the Muslim community, which is the aim of da'wah. The formulation of the problem in this research is: What are the indications of the realization of the value of monotheism in developing the spiritual mentality of Muslim communities? This qualitative research uses a descriptive approach; the researcher describes the interpretation of monotheism in Surah Al-Ikhlas to serve as the main basis for analyzing the mental and spiritual development of Muslim communities in Indonesia in particular. The findings that the author encountered were, first, that da'wah is not a way to seek popularity; second, da'wah is an obligation while its success is absolutely in God's hands; and third, tawheed is the commander of Da'wah; there is no more powerful force capable of changing the order of society except a movement that only relies on God only.